2007
DOI: 10.1111/j.1746-1561.2007.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

School Food Practices of Prospective Teachers

Abstract: These findings suggest that knowledge, attitudes, and food behaviors of prospective teachers may be barriers to promoting healthy food habits to their future students. Further, prospective teachers would benefit from policies and programs that support healthy classroom practices and from compulsory nutrition education in the teacher training curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
2
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 7 publications
3
52
2
4
Order By: Relevance
“…6,18 A study that assessed future teachers’ intended classroom food practices found one half of them would use candy or pizza as a reward for students in their future classrooms. 5 Since preschool children’s food preferences are established through repeated food exposure and the social context in which they consume the food, offering unhealthful foods such as candy as an incentive promotes preference for this food and reinforces unhealthful behaviors. 18‐20 In addition to repeated exposure, offering sweet and non-sweet snacks as rewards may increase preference for these foods among preschool children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,18 A study that assessed future teachers’ intended classroom food practices found one half of them would use candy or pizza as a reward for students in their future classrooms. 5 Since preschool children’s food preferences are established through repeated food exposure and the social context in which they consume the food, offering unhealthful foods such as candy as an incentive promotes preference for this food and reinforces unhealthful behaviors. 18‐20 In addition to repeated exposure, offering sweet and non-sweet snacks as rewards may increase preference for these foods among preschool children.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their authority status and the amount of time they spend with students, teachers are important role models through their own eating behaviors and beliefs and classroom food practices. 5,6 This is particularly relevant in kindergarten and first grade when children are first exposed to the school environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two groups of researchers (Rafiroiu & Evans, 2005;Rossiter et al, 2007) brought out the need for teachers to model good nutrition behaviours to learners. Harnessing the strength of teachers to improve learners' dietary behaviours can significantly reduce children at risk of morbidity from obesity and other malnutrition diseases.…”
Section: Implication For Researchmentioning
confidence: 99%
“…Teachers who received training to implement nutrition education were better equipped to teach nutrition concepts to learners effectively. Teachers represent authority figures and role models to learners and for this reason can model healthy dietary behaviours (Rossiter et al,2007). Moreover, teachers have the opportunity to integrate nutrition issues into other subjects thereby using a multi-faceted approach to emphasise nutrition messages (Panunzio et al, 2007).…”
Section: Training Of Teachersmentioning
confidence: 99%